Translation and highlighting of illocutionary force: the case of negative questions - Hernández, C. Patricia (Romanica Olomucensia, 2014)
This study proposes an examination of the interrogative form and more particularly negative questions. These structures are not a mere stylistic device equal to the positive form: they have an illocutionary force which plays a central role in the interaction. The aim of this paper is to show that the translator highlights the illocutionary force he perceives in the interrogative sentence by the use of the negative form. After a summary presentation of the description given by the linguistic literature, this work focuses on the translation of interrogative sentences and the choice by the translator of negative questions. We will analyze the translation from Spanish to French of interrogative sentences taken from the novel Boquitas pintadas (Puig 1968) and we will specially consider the change from positive to negative questions. It is argued that this operation underlines the translator's subjectivity.
Keywords: Spanish French translation; negative questions; illocutionary force; subjectivity.